(untitled) (Mustansiria Dental Journal, 2018)
Aim: The aim of this in vitro study was to evaluate the antimicrobial action of four resin based endodontic sealers after 24 hrs. Materials and Method: The freshly mixed sealers were AH26, AH-plus, Epiphany and Topseal. They were prepared according to manufacturer’s instruction and placed in prepared wells of 40 agar plates inoculated with Streptococcus viridans, Staphylococcus aureus and Enterococcus faecalis. (10 samples for each microorganism). Four cavities, each one measuring 5 ml in diameter and 4 ml in depth, were made in each agar plate using cork poorer. Agar diffusion method on Muller Hinton agar was employed, and zones of inhibition were measured after 1day. Results: AH26 containing proved to be the most effective against all microorganisms tested. This was followed by Epiphany. Topseal which showed antibacterial activity on all tested microorganisms slightly higher than that of AH-Plus which showed the least action on all tested microorganisms. Conclusion: All the sealers evaluated in this study showed different inhibitory effect against all bacterial strains.